Distribution and source identification of polycyclic aromatic hydrocarbons in mangrove sediments and pneumatophores in Rembau-Linggi estuary, Malaysia - Raza, Muhammad (2012)
Polycyclic aromatic hydrocarbons (PAHs) are one of the foremost widespread classes of pollutants which can accumulate in sediments for a long period of time due to their low water solubility and hydrophobicity properties. Mangrove sediment acts as a sink for organic pollutants especially in an estuary environment. The aims of this study are to determine the composition, distribution and sources of P AHs in mangrove sediments and pneumatophores of Sonneratia in Rembau-Linggi estuary. The samples were collected from nine stations along Rembau-Linggi estuary, Negeri Sembilan. The samples were then extracted using a soxhlet extractor with dichloromethane followed by silica gel column chromatography to separate the hydrocarbons into fractions. The 17 P AHs were analyzed and identified using GCMS based on the response factor of a P AH standard. Low molecular weight P AHs were abundant in pneumatophores while high molecular weight P AHs were abundant in sediments. Total P AHs in pneumatophores were significantly higher (p<0.05) than in sediments in all eight stations. There is no significant correlation between P AHs and organic carbon which means that the distribution of P AHs was not affected by the organic carbon content. Total methylphenanthrenes (MP) shows weak correlation with total P AHs (p<0.05) implying that petrogenic input has some contribution to the sedimentary P AHs but not a major control over distribution of P AHs within the estuary. CombPAH shows a positive correlation with total P AHs with R2=0.9368 (p<0.05) suggesting that pyrogenic input has significant contribution to the sedimentary PAHs. It is suggested that the combustion of petroleum, wood and coal were the main sources of P AHs which have been brought by long-range atmospheric transport and thus, deposited into this estuary. The P AH concentrations increased with distance from upstream of the estuary to the coastal area of Straits of Malacca which implied that river discharge and urban runoff flowing from residential areas centred near the coastline of the Straits of Malacca were the probable source of P AHs. There is a moderate relationship between P AHs of sediments and pneumatophores (p<0.05) which implied that sedimentary P AHs have moderate influence on the P AH distribution in pneumatophores. None of individual PAH compounds exceeded the values of ERL-ERM and TEL-PEL guidelines thus P AH level in sediments in Rembau-Linggi estuary are unlikely to cause any adverse biological effects to aquatic organisms.